A Rare Flexible Metal–Organic Framework Based on a Tailorable Mn8‐Cluster Showing Smart Responsiveness to Aromatic Guests and Capacity for Gas Separation. Issue 26 (5th April 2022) - Wang, Wei; Xiong, Xiao‐Hong; Zhu, Neng‐Xiu; Zeng, Zheng; Wei, Zhang‐Wen; Pan, Mei; Fenske, Dieter; Jiang, Ji‐Jun; Su, Cheng‐Yong
Abstract: The design and creation of soft porous crystals combining regularity and flexibility may promote potential applications for gas storage and separation due to their deformable framework's responsiveness to external stimuli. The flexibility of metal–organic frameworks (MOFs) relies on alterable degrees of freedom that are mainly provided by organic linkers or the junctions linking organic and inorganic building units. Herein, we report a new dynamic MOF whose flexibility originates from an unprecedented tailorable Mn8 O38 ‐cluster and shows simultaneous coordination geometry changes and ligand migration that are reversibly driven by guest exchange. This provides an extra degree of freedom to the framework's deformation, resulting in three‐dimensional variations in the framework that subtly respond to varied aromatic molecules. The gas adsorption behavior of this flexible MOF was evaluated, and the selective separation of light hydrocarbons and Freon gases is achieved. Abstract : An extra degree of freedom to framework flexibility contributed by size‐ and shape‐tailorable metal clusters is established, leading to three‐dimensional variations of the framework that are smartly responsive to varied aromatic molecules.